Camptoplax ahmar sp. nov., a new pilumnid crab (Crustacea: Brachyura) from the Red Sea - Ng, Peter K. L.; Anker, Arthur (Zootaxa, 2024)
Camptoplax ahmar sp. nov. is described based on a single male specimen extracted from a burrow of an unknown host near Thuwal, Red Sea coast of Saudi Arabia. The new species differs from the type-species of Camptoplax Miers, 1884 and its only congener, C. coppingeri Miers, 1884, by several morphological / morphometric details.